2013
DOI: 10.4049/jimmunol.1301458
|View full text |Cite
|
Sign up to set email alerts
|

CD55 Costimulation Induces Differentiation of a Discrete T Regulatory Type 1 Cell Population with a Stable Phenotype

Abstract: Unlike other helper T cells, the costimulatory ligands responsible for T regulatory type 1 (Tr1) cell differentiation remain undefined. Understanding the molecular interactions driving peripheral Tr1 differentiation is important because Tr1s potently regulate immune responses by IL-10 production. In this study, we show that costimulation of human naive CD4+ cells through CD97/CD55 interaction drives Tr1 activation, expansion, and function. T cell activation and expansion was equipotent with CD55 or CD28 costim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 53 publications
(60 reference statements)
1
24
0
Order By: Relevance
“…However, the extent of the inflammation is not as severe as in other EO-IBD patients. The origin of the inflammation is still unclear, but we propose 2 potential pathomechanisms: dysregulation of immunoregulatory T cells, similar to observation made in mouse models on the role of CD55 on T reg homeostasis,169 and epithelial and/or endothelial barrier damage due to complement activation. Interestingly, some patients develop thrombotic events, a clinical manifestation of many complementopathies.…”
supporting
confidence: 64%
“…However, the extent of the inflammation is not as severe as in other EO-IBD patients. The origin of the inflammation is still unclear, but we propose 2 potential pathomechanisms: dysregulation of immunoregulatory T cells, similar to observation made in mouse models on the role of CD55 on T reg homeostasis,169 and epithelial and/or endothelial barrier damage due to complement activation. Interestingly, some patients develop thrombotic events, a clinical manifestation of many complementopathies.…”
supporting
confidence: 64%
“…generated in vitro can be purified from bulk cultures using CD49b and LAG-3 antibodies (Amodio et al, 2015;Gagliani et al, 2013b;Mfarrej et al, 2017;Petrelli et al, 2015). The frequency of CD4 + CD45RA -CD49b + LAG-3 + cells correlates with the expression of IL-10 in human (Amodio et al, 2015;Mfarrej et al, 2017;Petrelli et al, 2015;Sutavani et al, 2013;Tousa et al, 2017;Yao et al, 2015;Tousa et al, 2017), and with induction of immunological tolerance in different preclinical and clinical settings Gagliani et al, 2013b;Kim et al, 2018;Koch et al, 2015;Zhu et al, 2018). Using single-cell mass cytometry, we have shown that CD49b and LAG-3 were sufficient to identify a population of CD4 + CD45RAcells, which is distinct from Th1, Th2, Th17, Tfh, and Treg cells.…”
Section: Phenotype Of Murine and Human Tr1 Cellsmentioning
confidence: 99%
“…20,26,30,31 Third, co-stimulatory molecules such as ICOS ligand (ICOS-L), CD46, CD2, and CD55 are involved in the differentiation of Tr1 cells. 30,[32][33][34] It has also been showed that the long-term interactions of GITR/GITRL signaling boosted Tr1-cell differentiation and expansion in mice in vivo. 35 Zohar et al believed that chemokine (C-X-C motif) ligand 11/chemokine receptor 3 (CXCL11/CXCR3) interaction may induce transformation of CD4…”
Section: In Vitro Induction Of Tr1 Cellsmentioning
confidence: 99%